Different mCherry isoforms show distinct photophysical properties in FRET tandem constructs - Hoffmann, Birgit; Melle, Christian; Biskup, Christoph (Frontiers in Bioengineering and Biotechnology, 2025)
Fluorescent proteins are important reporter tools to investigate biological processes in the cellular environment at the molecular level. The spectrum of available fluorescent proteins has been greatly expanded by red-emitting fluorescent variants such as the commonly used mCherry. However, the presence of alternative translation initiation sites (aTIS) in mCherry allows for production of shorter protein isoforms with different properties that can bias the results of studies in which mCherry intensities are evaluated. In the present study, we used a novel approach of spectroscopic techniques, including Förster resonance energy transfer (FRET) to investigate the impact of aTIS on the photophysical properties and the functionality of mCherry in both, prokaryotic and eukaryotic expression systems. To this aim, FRET tandem constructs with different translation initiation sites, comprising mNeonGreen as donor fluorophore and mCherry as acceptor, were designed and systematically analyzed using steady-state spectroscopy, time- and spectrally-resolved fluorescence measurements, and fluorescence lifetime imaging (FLIM) based FRET measurements. The long isoforms exhibited similar photophysical properties like the full-length mCherry protein. They were also suitable FRET acceptors when coupled to mNeonGreen. The choice of translation initiation site markedly affected donor fluorescence lifetime, fluorescence intensity, and efficiency of energy transfer of the FRET constructs. Longer mCherry isoforms retained FRET acceptor functionality whereas shorter translational isoforms were non-functional, i.e., were non-fluorescent and had no effect on donor fluorescence lifetime. Our results provide insight into the implications of aTIS when using mCherry as fluorescent reporter. Overall, our study highlights the importance of considering translation initiation mechanisms in both pro- and eukaryotic systems, as they can substantially impact protein functionality and the interpretation of biological measurements.